BAURAN PROMOSI (PROMOTION MIX) KONVENSIONAL DALAM PERSPEKTIF ETIKA BISNIS ISLAM - Nur Wanita (Fakultas Syariah Institut Agama Islam Negeri Palu, 2016)
One of marketing strategy policy that is used by companies to face their competitors is through promotion mix. In this case, each company has its own promotion mix policy which is diverse, this policy that is aimed to obtain company’s targets in market particularly to attract and fascinate consumers for the products, through this competition, it is not a few number of company who takes shortcuts and justifies any means in order to meet their goals; to earn profits, hence they tend to violate ethic. Islamic business ethic concept does not have any rivalry concept that is likely to ruin others unless synergize and cooperate one another. The variety of products from different manufacturers can offer alternative convenience for the consumers to get products according to their needs and capabilities.